Observations on the Breeding Behaviour of Phalaropes - Höhn, E.O. (ARCTIC, 1968)
On 27 May 1967, I reached the settlement of Chesterfield Inlet (Igluliarjuk), Keewatin, Northwest Territories. No phalaropes were seen in the district until 13 June. On that day, red phalaropes (Phalaropus fulicarius) in considerable numbers and some northern phalaropes (P. lobatus) were seen at sea in the offing of, or flying over, one of the islets in the mouth of the inlet. During the next 10 days, phalaropes of both species used a mainland lagoon near the settlement, but their number here gradually declined and by the end of June they had deserted this locality completely. Some northern phalaropes nested on the mainland and others of this species at least attempted to nest on Promise Island (Nannuyuma), where 5 pairs of red phalaropes nested and a sixth pair made a nest (but apparently no eggs were laid). After the local spring passage, red phalaropes were seen only on Fairway (Pitiulaktok) and Promise islands. Breeding may well have taken place on Fairway, but a visit there at the appropriate time was not possible. The apparent definitive departure of the females from Promise Island after egg laying was observed on the night of 9-10 July. The newly hatched young of 1 pair still in the nest and guarded only by a male were found at this breeding station on 20 July. Three other males acted as if they had young hidden near the nests which were, by that time, empty. The eggs in the fifth nest had not hatched and this nest had evidently been deserted by the male. The 4 downy young found were weighed and banded. Confirming my earlier observations on Wilson's phalarope, no territorial behaviour was shown by red phalaropes on the mainland or on Promise Island. The association of red phalarope nesting with colonially breeding arctic terns (Sterna paradisaea), reported by Løvenskiold, as frequently observed in the Svalbard Archipelago (Spitsbergen), also applied to Promise Island. . Local Eskimo bird and mammal names were collected in the Chesterfield Inlet area, and at Baker Lake a list restricted to bird names was ...